Restaging the Past Historical Pageants, Culture and Society in Modern Britain - Bartie, Angela; Fleming, Linda; Freeman, Mark; Hutton, Alexander; Readman, Paul (UCL Press, 2020)
Restaging the Past is the first edited collection devoted to the study of historical pageants in Britain, ranging from their Edwardian origins to the present day. Across Britain in the twentieth century, people succumbed to 'pageant fever'. Thousands dressed up in historical costumes and performed scenes from the history of the places where they lived, and hundreds of thousands more watched them. These pageants were one of the most significant aspects of popular engagement with the past between the 1900s and the 1970s: they took place in large cities, small towns and tiny villages, and engaged a whole range of different organised groups, including Women's Institutes, political parties, schools, churches and youth organisations. Pageants were community events, bringing large numbers of people together in a shared celebration and performance of the past; they also involved many prominent novelists, professional historians and other writers, as well as featuring repeatedly in popular and highbrow literature. Although the pageant tradition has largely died out, it deserves to be acknowledged as a key aspect of community history during a period of great social and political change. Indeed, as this book shows, some traces of 'pageant fever' remain in evidence today.